Studi Komparatif Perilaku Nonlinear Slender Shearwall Dan Squat Shearwall Terhadap Beban Dinamik - Ryan Wijaya; Yoyong Arfiadi (Jurnal Impresi Indonesia, 2025)
his study aims to conduct a comparative investigation of two types of reinforced concrete shear walls namely, slender shearwalls and squat shearwalls in order to understand the differences in their dynamic responses and hysteretic behavior under seismic loading. The analysis was performed through a numerical approach using time history simulation in the OpenSees software, with the El Centro earthquake record as input. The study focuses on evaluating structural displacement, force, rotation, moment, and ductility based on force-displacement and moment-rotation relationships. The results indicate that the slender shearwall exhibits larger displacement responses, more significant plastic rotations, and better ductility performance in the positive direction. Conversely, the squat shearwall demonstrates greater lateral stiffness and strength, along with higher ductility in the negative direction. The hysteretic characteristics of both wall types further reflect the dominance of different structural mechanisms slender shearwalls tend to exhibit flexural behavior, while squat shearwalls are primarily governed by shear action. Overall, the simulation results reveal that each shearwall type has its own distinctive advantages. The slender shearwall is more effective in accommodating plastic deformation, whereas the squat shearwall excels in resisting large lateral forces with limited deformation. These findings are expected to serve as a reference for the design of shear wall systems in earthquake-resistant buildings, particularly in Indonesia.